Edukasi Pengetahuan Simpati (Sosialisasi Dan Intervensi Masalah Anemia Pada Remaja Lewat Asuhan Tepat Dan Inovatif) Di Puskesmas Kibang Budi Jaya: Pengabdian - Esti Prajaningrum; Yona Desni Sagita; Nila Qurniasih; Rini Wahyuni; Laila Kurniawati; C Hardiyati Rukmana; Mayantika Fitrisa; Tri Widayanti; Sri Sulistyaningsih; Sumarni; Noviyana; Evi Wijayanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aimed to increase adolescent girls’ knowledge about anemia, including its causes, symptoms, impacts, and prevention efforts. The method used was an observational analytic design with a pretest–posttest approach involving 31 adolescent girls selected through random sampling. Data were collected using a questionnaire consisting of 15 questions, followed by an interactive health education session using leaflet media. The results showed that the mean knowledge score of respondents increased from 42.90 at the pretest to 80.65 at the posttest. The Wilcoxon test yielded a p-value = 0.000 (p < 0.05), indicating a significant difference before and after the intervention. These findings demonstrate that health education using leaflets is effective in improving adolescent girls’ knowledge about anemia. It is recommended that adolescent girls apply the information gained through balanced nutrition and adherence to Iron-Folic Acid (IFA) tablet consumption. Furthermore, health centers and health workers are encouraged to carry out continuous education, strengthen the school-based IFA supplementation program, and monitor adherence as a sustainable strategy for anemia prevention.